Coordination Compounds of Cerium(III) Chloride with Oxygen and /or Nitrogen Donor Ligands - Trikha, A.K.; Kumar, A. (Asian Journal of Chemistry, 2010)
Coordination compounds of cerium(III) chloride with various oxygen and/or nitrogen donor ligands like aliphatic amines, morpholines, piperidines and pyrazole have been prepared and characterised on the basis of elemental analysis infrared and electronic spectral studies. Three types of complexes 2 : 1, 1 : 1 and 1 : 2 are formed.